EDUKASI LITERASI KEUANGAN - Novia Utami; Siti Saadah; Marsiana Luciana Sitanggang; Teresia Angelia Kusumahadi (Jurnal Bakti Masyarakat Indonesia, 2022)
The program literacy education program aims to increase the knowledge, understanding, and access of the Indonesian people to financial institutions, products, and services. Based on the results of a survey conducted by the Financial Services Authority in 2019, the financial literacy index in Indonesia is still low and only reached 38,03%. The educational program that we organized online through the Zoom platform is intended to support the improvement of public financial literacy, especially the students of SMA Santo Yakobus. They are part of the millennial generation of potential investors who must be given knowledge and understanding about the characteristics, benefit, and risks of various investment instruments that continue to develop from time to time. Attention to the millennial generation is important because data shows that currently the millennial generation is starting to dominate investment activities in several important financial assets. Based on the results of of a descriptive analysis of the respondent’s data on training participants, although they are not yet financially independent, more than 95% of them stated that the training has opened their horizons regarding I have nvestment activity in financial assets. The average score of 3 in the post-test for aspects of financial knowledge, financial behavior, and financial attitude, confirms their statement. The more people who have good financial knowledge, the greater the role of the financial sector in financing the investment in the real sector.ABSTRAKProgram Edukasi Literasi Keuangan bertujuan untuk meningkatkan pengetahuan, pemahaman, dan akses masyarakat Indonesia terhadap lembaga, produk, dan layanan jasa keuangan. Berdasarkan hasil survei yang dilakukan oleh Otoritas Jasa Keuangan pada tahun 2019, indeks literasi keuangan di Indonesia masih rendah dan baru mencapai angka 38,03%. Program edukasi yang kami selenggarakan secara online melalui platform Zoom, dimaksudkan untuk mendukung peningkatan literasi keuangan masyarakat, khususnya siswa-siswi SMA Santo Yakobus. Mereka adalah bagian dari generasi milenial calon investor potensial yang harus diberikan pengetahuan dan pemahaman tentang karakteristik, manfaat, dan risiko dari berbagai instrumen investasi yang terus berkembang dari waktu ke waktu. Perhatian terhadap generasi milenial menjadi penting karena data yang ada menunjukkan bahwa saat ini generasi milenial mulai mendominasi aktivitas investasi pada beberapa aset keuangan penting.  Berdasarkan hasil analisis deskriptif terhadap data responden peserta pelatihan, walaupun mereka belum mandiri secara finansial namun ternyata lebih dari 95% dari mereka menyatakan bahwa pelatihan telah membuka wawasan mereka terkait seluk beluk berinvestasi pada financial asset. Rerata skor 3 pada saat post-test untuk aspek financial knowledge, financial behaviour, dan financial attitude menguatkan pernyataan mereka tersebut. Semakin banyak masyarakat yang memiliki pengetahuan keuangan yang baik, maka semakin besar peran sektor keuangan dalam pembiayaan aktivitas investasi di sektor rii